DOI: 10.29007/x52h
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Skilled Trade Students on Factors Impacting the Decision to Pursue a Construction Career

Abstract: The construction industry is confronted with a critical shortage of skilled trade workers, which greatly hampers its growth and labor productivity. This shortage of workforce mainly stems from a lack of effective strategies for recruiting and retaining students in construction programs, which can be addressed by fully understanding major factors that influence student decisions to pursue a career in the industry. This study investigated the perceptions and opinions of students on developing a long-term career … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One of the other major issues facing the construction industry lies in the lack of skilled workers, which has digressed over time (Haupt & Harinarain, 2016;Ostadalimakhmalbaf et al, 2021;Windapo, 2016). Research shows that the South African education system does not produce the required graduates with the desired demographics to implement employment equity; moreover, the sector and the country are experiencing a loss of critical developmental skills (Akinradewo et al, 2022;SAFCEC, 2019).…”
Section: Objectivesmentioning
confidence: 99%
“…One of the other major issues facing the construction industry lies in the lack of skilled workers, which has digressed over time (Haupt & Harinarain, 2016;Ostadalimakhmalbaf et al, 2021;Windapo, 2016). Research shows that the South African education system does not produce the required graduates with the desired demographics to implement employment equity; moreover, the sector and the country are experiencing a loss of critical developmental skills (Akinradewo et al, 2022;SAFCEC, 2019).…”
Section: Objectivesmentioning
confidence: 99%
“…A recent study found that only 66% of people had a well-founded understanding of compensation rates in construction career pathways and 32% of high-school students have a negative opinion of the construction industry (Ostadalimakhmalbaf, et al, 2021). The same study also reported that "improved family-unit perception of the construction-related programs and careers" is a top issue to be addressed.…”
Section: Introductionmentioning
confidence: 99%